Analisis Akad Ijarah pada Jasa Rias Pengantin dalam Perspektif Fiqih Muamalah - Istiqomah, Istiqomah; Hidayati, Tri (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the application of ijarah contracts in the practice of bridal makeup services at YW, Palangka Raya city, in the perspective of fiqh muamalah. Bridal makeup services are a form of rental contract for services (ijarah) that is commonly practiced in the community, but it is still rarely studied in depth in terms of Islamic law. This research uses a qualitative method with a descriptive-analytical approach, and data is collected through observation, interviews, and literature study. The results show that the practice of ijarah contract in YW has fulfilled all the pillars and conditions of ijarah according to fiqh provisions, such as the existence of ijab-qabul, clear benefits, agreed compensation (ujrah), and voluntary agreement of both parties. In the case of unilateral cancellation by the client, the forfeiture of the down payment is in accordance with sharia principles as compensation for the loss of the service provider. This research confirms that ijarah contracts in the context of bridal makeup services can be carried out in a sharia-compliant manner and become a fair transaction model in a sharia-based service economy.